Airflow field simulation model building and application for aerobic compost using CFD - Cheng, Qiongyi; Meng, Haibo; Zhou, Haibin; Shen, Yujun; Cheng, Hongsheng; Ding, Jingtao; Zhao, Shihao; Hou, Shance (International Journal of Agricultural and Biological Engineering, 2021)
Composting is a suitable low-cost strategy to transform animal waste into a stabilized end product, and the airflow field in the pile affects the fermentation states. For piles in the aeration weak zone, anaerobic fermentation may happen as the lack of oxygen. While in practice, due to the extremely low speed and harsh condition, the airflow field was scarcely researched. This study adopted Computational Fluid Dynamics (CFD) to investigate the airflow field in the compost pile. A three-dimensional CFD model was built; the compost pile in this model was simplified as porous media; unstructured mesh was adopted to discretize the geometric model; standard k-ε model and SIMPLE scheme were employed for numerical methods. The CFD model was validated with the field experiment in the cooling period. Then the model was applied to research the airflow field in the pile with increased pipe diameter. Results showed that it was feasible to investigate the airflow field in the pile with CFD. For boundary conditions in the CFD model, treating the compost pile as a homogeneous porous media is reasonable. The CFD model was successfully validated by the field measurement (the average relative difference between the simulated and measured air speed was within 10%). Airflow in the existing compost pile showed nonuniform distribution with stagnation and vortex zones; the turbulence intensities were 3.57 and 1.43 for the airflow in the pile and the reactor, respectively. When pipe diameter increased, the airflow distribution uniformity in the pile was improved significantly. With diameter raising to 0.04 m, the turbulence intensity decreased to 1.54 and 0.42 for the airflow in the pile and the reactor, respectively. The CFD model developed in this research can provide qualitative and quantitative analyses of the airflow field in compost piles, and can be a theoretical basis for the aeration system design. Keywords: CFD, model building, compost, airflow field, pile DOI: 10.25165/j.ijabe.20211404.6087 Citation: Cheng Q Y, Meng H B, Zhou H B, Shen Y J, Cheng H S, Ding J T, et al. Airflow field simulation model building and application for aerobic compost using CFD. Int J Agric & Biol Eng, 2021; 14(4): 245–254.